1991
DOI: 10.1093/rheumatology/30.5.370
|View full text |Cite
|
Sign up to set email alerts
|

Evening Primrose Oil in Patients With Rheumatoid Arthritis and Side-Effects of Non-Steroidal Anti-Inflammatory Drugs

Abstract: Forty patients with rheumatoid arthritis and upper gastrointestinal lesions due to non-steroidal anti-inflammatory drugs entered a prospective 6-month double-blind placebo controlled study of dietary supplementation with gamma-linolenic acid 540 mg/day. Nineteen patients received active therapy (as evening primrose oil 6 g/day) and 21 received placebo (olive oil 6 g/day). No patient stopped non-steroidal anti-inflammatory therapy but three patients in each group reduced their dose. Other results showed a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 0 publications
3
48
0
Order By: Relevance
“…In some of these studies improvements were also reported in the group treated with olive oil (46,47,60). The beneficial effect observed in these studies, may be attributed to the monounsaturated fatty acid (MUFA) oleic acid (OA; 18:1n-9), which constitutes a large proportion of the fatty acids present in olive oil.…”
Section: Dietary Supplementationmentioning
confidence: 93%
See 1 more Smart Citation
“…In some of these studies improvements were also reported in the group treated with olive oil (46,47,60). The beneficial effect observed in these studies, may be attributed to the monounsaturated fatty acid (MUFA) oleic acid (OA; 18:1n-9), which constitutes a large proportion of the fatty acids present in olive oil.…”
Section: Dietary Supplementationmentioning
confidence: 93%
“…A few studies indicate that supplementation with γ-linolenic acid (GLA; 18:3n-6) can lead to clinical improvement in RA patients (60)(61)(62)(63). Like n-3 fatty acids, an increased intake of GLA seems to alter the profile of eicosanoids in a favourable manner.…”
Section: Dietary Supplementationmentioning
confidence: 99%
“…Jantti et al [38] administered EPO (GLA dose not given) or olive oil in a double-blind randomized study to RA patients for 12 weeks and noted no difference in clinical improvement. Similarly, Brzeski et al [39] found no advantage using EPO (560 mg GLA/day for 6 months) vs. olive oil to treat RA patients. Pullman-Mooar et al [40] fed 1,125 mg of GLA/day in the form of BO for 12 weeks to 7 RA patients and 4 healthy controls.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Evening primrose oil has a high concentration of polyunsaturated fatty acids, in particular ␥ -linolenic acid (18: 3n-6), and has been used for more than 30 years as a dietary supplement [Hudson, 1984]. The beneficial effects of polyunsaturated fatty acids have been reported for various ailments such as rheumatic and arthritic conditions, atopic dermatitis, premenstrual and postmenopausal syndromes, and diabetic neuropathy [Brzeski et al, 1991;Berth-Jones and Graham-Brown, 1993;Cerin et al, 1993;Belch and Hill, 2000;Barre, 2001]. In addition, the mechanisms related to their actions have been studied in animal models [Engler, 1993;Dines et al, 1996] as well as humans [Ziboh and Chapkin, 1987;Ziboh et al, 2000].…”
Section: Inhibitory Effects Ofmentioning
confidence: 99%